CRITICAL ANALYSIS OF VATA DOSHA IN SUSHRUTA SAMHITA - Ashok, Kumar; B. K, Dwibedy (International Journal of Ayurveda and Pharma Research, 2015)
Ayurveda is the science of living beings which deal with maintenance of a healthy individual as well as removal of the diseases through which one can get the Sukha (happiness) and removal of Dukha (Miseries). There are three most auspicious books of Ayurveda or triad of Charaka samhita, Sushruta samhita and Ashtanga hridaya jointly known as Brihattrayi. Sushruta samhita is written by Acharya sushruta (Vriddha sushruta). Sushruta has compiled and collected all the speech of lord Dhanvantari in a systematic form which became the famous book of Shalyatantra as a Sushruta samhita. Ayurveda stands on its own basic pillars and concepts regarding Doshas are one of them. Doshas are responsible for physiological actions in the body manifested as health and pathologically manifested as disease specially Vata dosha. Vatadoshas etymology has been described in two forms, aetiologies, separate group of diseases under Vatavyadhi, six stages of Kriyakala according to Vata dosha, characteristics of Vataprakritti etc. have been innumerated and analysis regarding Vata dosha in available Sushruta samhita has been presented in this paper.